1986
DOI: 10.1118/1.595840
|View full text |Cite
|
Sign up to set email alerts
|

The neutron dose and energy spectrum outside a 20‐MV accelerator treatment room

Abstract: A maze design is discussed for a Therac 20 linear accelerator (manufactured by Atomic Energy of Canada, Ltd.) which reduces the flux of neutrons at the door to permissible levels in controlled areas. The L-shaped design allows for a relatively light door at the end of the maze, consisting of 5.08-cm (2-in.) borated polyethylene and 2-mm lead. A comparison is made between the neutron dose equivalent (DE) calculated by various methods and the DE measured with a variety of portable neutron survey meters. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…It is seen that among the stud ied an a lyt i cal meth ods, the Wu-McGinley and then French meth ods pro vide better re sults com par ing to MC re sults for neu tron dose equiv a lents at the maze en trance door. The re sults were very sim i lar to the results of Mul ler-Runkel et al, who showed that the French method acts better than Ker sey and Mc Call meth ods in a ra di a tion ther apy room with 20 MeV pho tons [23]. Monte Carlo and ex per i men tal stud ies have shown that an a lyt i cal meth ods over es ti mate the neu tron dose equiv a lent at the maze en trance door [14].…”
Section: Re Sults and Discussionsupporting
confidence: 81%
“…It is seen that among the stud ied an a lyt i cal meth ods, the Wu-McGinley and then French meth ods pro vide better re sults com par ing to MC re sults for neu tron dose equiv a lents at the maze en trance door. The re sults were very sim i lar to the results of Mul ler-Runkel et al, who showed that the French method acts better than Ker sey and Mc Call meth ods in a ra di a tion ther apy room with 20 MeV pho tons [23]. Monte Carlo and ex per i men tal stud ies have shown that an a lyt i cal meth ods over es ti mate the neu tron dose equiv a lent at the maze en trance door [14].…”
Section: Re Sults and Discussionsupporting
confidence: 81%
“…of borated polyethylene, most of (n, ) interactions occurred with Boron atoms and gamma rays with average energy of 0.4 MeV released in the process. 15 In another study by Tochilin and LaRiviere, average energy of 3.6 MeV was reported for capture gamma rays. 20 Finally, capture gamma rays are found at the maze entrance door and their effect on maze entrance door shielding should be considered in radiation therapy facilities.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4] On the other hand, it is associated with unwanted photonuclear reaction between high energy photons and linac head materials, patient body and treatment room walls. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Production of photoneutrons occurs through photonuclear reactions, and consequently high energy gamma rays can be generated in the maze, following the capture process of thermalized neutrons. 16 Both photoneutrons and neutron capture gamma rays are considered as undesirable radiations from radiation protection point of view, because they increase the patient and staff whole body radiation dose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι μέθοδοι αυτές βασίζονται σε πειραματικές μετρήσεις, λαμβάνοντας υπόψη τα επιμέρους γεωμετρικά χαρακτηριστικά των θαλάμων. Ωστόσο έχουν παρατηρηθεί σημαντικές διαφορές ανάμεσα στα αποτελέσματα των υπολογισμών και των πειραματικών μετρήσεων (Muller-Runkel et al 1986). Ειδικότερα, σε περιπτώσεις θαλάμων θεραπείας ειδικής κατασκευής οι διαφορές αυτές είναι μεγάλες και οι ημιεμπειρικές τεχνικές προσδιορισμού της δόσης στο θάλαμο θεραπείας δεν μπορούν να εφαρμοστούν.…”
Section: εισαγωγηunclassified